Rapid Testing of Food Matrices for Bacillus cereus Enterotoxins. Issue 1 (7th June 2016) - Tallent, Sandra M.; Hait, Jennifer M.; Knolhoff, Ann M.; Bennett, Reginald W.; Hammack, Thomas S.; Croley, Timothy R.
Abstract: Nine different food products frequently associated with Bacillus cereus outbreaks were chosen as representative matrices to be evaluated with end‐point polymerase chain reaction (PCR), enzyme linked immunosorbent assay, lateral flow device and mass spectrometry for detection of enterotoxins associated with human illness. Testing was performed on food portions inoculated with a bacterial strain and incubated at 30°C for either 5 h or 24 h. A screening end‐point multiplex PCR targeting enterotoxin genes including the emetic toxin and three diarrheal toxins, hemolytic hemolysin BL (Hbl), nonhemoltyic enterotoxin (Nhe), and cytolysin K. Commercially available kits were used to determine the presence/absence of Nhe and Hbl. Finally; a quantitative analysis using mass spectrometry was performed for the detection of the emetic toxin. Definitive results were available after a five hour pre‐enrichment in five food products. The following strategy would allow for more efficient testing of surveillance or environmental samples as well as more rapid response time during a foodborne outbreak. Practical Applications: The application of a strategy for processing and analyzing food products for Bacillus cereus and the enterotoxins associated with foodborne illness was explored. Employment of such a strategy will decrease time spent processing negative samples allowing more time for analysis of potentially positive food products.